Anterior compartment mesh: a descriptive study of mesh anchoring failure. (24th October 2013) - Shek, K. L.; Wong, V.; Lee, J.; Rosamilia, A.; Rane, A. J.; Krause, H.; Goh, J.; Dietz, H. P.
ABSTRACT Objectives To define types of support failure after anterior compartment mesh placement and to investigate any association with predictors of recurrence. Methods This was a retrospective study on patients ≥ 3 months after anterior mesh placement. All patients underwent a standardized interview, clinical examination using the International Continence Society Pelvic Organ Prolapse Quantification system (ICS POP‐Q) and three‐dimensional/four‐dimensional (3D/4D) translabial ultrasound. Mesh failure was defined as recurrence of anterior/central compartment prolapse seen on ultrasound. Failures were classified as anterior, global and apical. Their association with hiatal area on Valsalva maneuver and levator avulsion was tested. Results Three hundred and one patients were seen initially, of whom five were excluded because of missing data, leaving 296. Mean follow‐up was 1.8 (range, 0.3–5.6) years. Mean age was 65 (range, 32–88) years. One hundred and thirty-nine (47%) women were fitted with a PerigeeTM mesh, 66 (22%) with an Anterior ProliftTM mesh and 91 (31%) with an Anterior ElevateTM mesh. Recurrent symptoms (lump/drag) were reported in 65 (22%), a recurrent cystocele was noted in 128 clinically (43%) and in 105 on ultrasound (35%). Avulsion was diagnosed in 117 patients (40%). Mean hiatal area on Valsalva was 33.3 (range, 14.1–60.0) cm2. Mesh failure was diagnosed in 112 patients (38%), comprising global failure in 81 (27%), apical failure in 23 (8%) and anterior failure in eight (3%). Apical and global failures were significantly associated with hiatal area, associations that remained after controlling for potential confounders. Conclusions Mesh failure, i.e. anterior or central compartment recurrent prolapse, was noted in 38% of patients on average 1.8 years after placement of anterior compartment mesh. Global and apical failures together constituted 93% of all mesh failures, both types of failure being significantly associated with hiatal area on Valsalva maneuver. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.